The Ratio of Three Means of Protecting the Interest of the Owner (Eurasian Research Bulletin, 2023)
In civil law, a few means of protecting the rights of the owner have been formed. Among them, the methods of vindication, restitution and condiction are widely applicable and have been known since the time of Roman private law. However, although general ideas about them have been formed, specific criteria for their application have not been developed, what remedies should be applied in what situation – the rules regulating this issue in detail have not been formed either in legislation or in judicial practice. This article reveals the essence of restitution, vindication and condiction, as well as issues related to their ratio, as ways to protect the rights of the owner.